Plasma Processing of Electrospun Li‐Ion Battery Separators to Improve Electrolyte Uptake. Issue 1 (27th November 2015) - Laurita, Romolo; Zaccaria, Marco; Gherardi, Matteo; Fabiani, Davide; Merlettini, Andrea; Pollicino, Antonino; Focarete, Maria Letizia; Colombo, Vittorio
Abstract : Atmospheric pressure non‐equilibrium plasma treatments of poly(vinylidene fluoride) (PVdF) solutions and electrospun Li‐ion separators are implemented to improve fiber morphology and increase electrolyte uptake. Plasma pre‐treatment of PVdF solutions increased the viscosity and induced a morphological change of polymer chains, enabling the production of defect‐free mats with improved mechanical properties compared to those produced from non pre‐treated solutions. The post‐treatment of the electrospun separator induced a chemical modification of the PVdF surface and an increase of electrolyte uptake. A synergistic effect between the plasma treatments is reported: the electrolyte uptake of the pre&post‐treated separators is about 1200%, ten times larger than that of commercial Celgard separators. Abstract : Plasma treatment of electrospun PVdF separator increases electrolyte uptake ten times larger than commercial Celgard.